Compassion in healthcare: a concept analysis. Issue 4 (19th July 2017) - Taylor, A.; Hodgson, D.; Gee, M.; Collins, K.
Abstract: Background: Compassion and compassionate care are central to radiographers' professional policy and practice and are congruent with the core values of the National Health Service Constitution. The term compassion however is over-used, ambiguous and vague. This work sought to explore and provide contextual understanding to the term compassion in healthcare. Method: Walker and Avant's eight-step model was used as the framework for the concept analysis. Data collection utilised a number of resources including online databases: Medline, CINAHL complete, Scopus, PubMed, PsycINFO, ScienceDirect, Cochrane and DARE; dictionaries, social media, Internet sources, books and doctoral theses. In all, 296 resources were included in the review. Results: The concept analysis distinguishes the defining characteristics of compassion within a healthcare context, allowing for associated meanings and behaviours to be outlined aiding understanding of compassion. Compassion in healthcare requires five defining attributes to be present: recognition, connection, altruistic desire, humanistic response and action. Conclusion: The findings identify the complexity of the term and subjective nature in which it is displayed and in turn perceived. The concept analysis forms the basis of further research aiming to develop a healthcare explicit definition of compassion within healthcare, specifically cancer care and radiography practices. Lucidity will enhance understanding, facilitating active engagement and implementation into practice.